2005
DOI: 10.1063/1.1935130
|View full text |Cite
|
Sign up to set email alerts
|

Sunlight stability of organic light-emitting diodes

Abstract: This paper reports on the photodegradation of organic light-emitting diodes (OLEDs) due to exposure to visible and near-ultraviolet light. Such exposure affects strongly the device performance, e.g., the electroluminescence intensity and the device current decrease considerably, however, the photoluminescence remains unaffected. This photodegradation was investigated on various production-relevant classes of high-quality polymer semiconductors with different energy gaps, i.e., a yellowish-green polyphenylenevi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 4 publications
0
21
0
Order By: Relevance
“…It was found that the polymer itself (at different absorption wavelengths) does not degrade. 310,455 This nonreactivity of the organic materials was proven by PL intensity measurements, where no changes in the PL luminance between aged and unaged samples are visible, whereas the EL properties are significantly altered. On the basis of these investigations, it was assumed that these light-caused reactions occur at the corresponding ITO−organic interface.…”
Section: Photochemical Reactionsmentioning
confidence: 96%
“…It was found that the polymer itself (at different absorption wavelengths) does not degrade. 310,455 This nonreactivity of the organic materials was proven by PL intensity measurements, where no changes in the PL luminance between aged and unaged samples are visible, whereas the EL properties are significantly altered. On the basis of these investigations, it was assumed that these light-caused reactions occur at the corresponding ITO−organic interface.…”
Section: Photochemical Reactionsmentioning
confidence: 96%
“…The photodegradation was investigated on various production-relevant classes of highquality organic semiconductors with different energy gaps, i.e., a yellowish-green polyphenylenevinylene derivative, red polyfluorene derivative, and blue polyspiro derivative. 127 The results demonstrated that the action spectrum of the photodegradation is strongly correlated with the fundamental absorption of the organic itself. Irradiation light with an energy larger than the electronic gap of the semiconducting organic leads to a degradation of the electroluminescence.…”
Section: Photodegradationmentioning
confidence: 95%
“…127 Such exposure affects strongly device performance, e.g., reductions of electroluminescence intensity and device current, however, the photoluminescence remains unaffected. The photodegradation was investigated on various production-relevant classes of highquality organic semiconductors with different energy gaps, i.e., a yellowish-green polyphenylenevinylene derivative, red polyfluorene derivative, and blue polyspiro derivative.…”
Section: Photodegradationmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] One of the main problems of PPVs, and conducting polymers in general, is their low stability under operation conditions due to the reactivity of the corresponding radical cations with oxygen and water, leading to degradative pathways. [8][9][10][11][12] One possibility for increasing the stability of PPV and related conjugated polymers is to incorporate them into the voids of porous solids. [13][14][15][16][17][18] By confinement in a restricted space, the accessibility of external reagents to the generated radical cations is minimized and, as a consequence, an increase in stability is observed.…”
Section: Introductionmentioning
confidence: 99%